Answer:
The answer to your question is letter B
Explanation:
a. f(x) = (x + 4)(x + 3)(x + 5) The zeros of this polynomial are x = -4, x = -3 and x = -5, so this polynomial is not the right answer,
b. g(x) = (x + 4)(x – 3)(x – 5) The zeros of this polynomial are x = -4, x = 3, x = 5, so this polynomial is the right answer.
c. h(x) = (x – 4)(x – 3)(x – 5) The zeros of this polynomial are x = 4, x = 3, x = 5, so this polynomial is not the right answer.
d. k(x) = (x – 4)(x + 3)(x + 5) The zeros of this polynomial are x = 4, x = -3, and x = -5, so this polynomial is not the right answer.